Digital biomarkers for depression screening with wearable devices: cross-sectional study with machine learning modeling - Rykov, Yuri (2022)
Background: Depression is a prevalent mental disorder that is undiagnosed and untreated in half of all cases. Wearable activity trackers collect fine-grained sensor data characterizing the behavior and physiology of users (ie, digital biomarkers), which could be used for timely, unobtrusive, and scalable depression screening.